Prvih pet besed slovenskih dojenčkov in malčkov v pričakovanem razvoju - Jelenc, Nika (Rehabilitacija (Ljubljana), 2021)
Background: A child's first word is a highly memorable moment for parents and an important indicator of early linguistic, social, and conceptual development. The study aimed to investigate the age of acquisition for the first five words Slovenian-speaking infants and toddlers say and the lexical and semantical characteristics of those words. Methods: An online survey was conducted with 126 parents of Slovenian preschool children about early expressive vocabulary. The survey focused on the first five words and the age at which these words were said. Results: The analysis of parental responses showed that the first word in more than half of infants and toddlers occurred before their first birthday. The vast majority, 90 % of toddlers in our sample, had already said at least five words before the age of 18 months. Nouns were the most common word class, followed by verbs and adverbs. Among the first five words, those for naming people from a child’s close environment predominated words for naming other objects and actions. Gender was not statistically significantly associated with the age at first-word acquisition or word-class selection. Conclusion: The research provides an insight into the understanding of ka Abstract Background: A child's first word is a highly memorable moment for parents and an important indicator of early linguistic, social, and conceptual development. The study aimed to investigate the age of acquisition for the first five words Slovenian-speaking infants and toddlers say and the lexical and semantical characteristics of those words. Methods: An online survey was conducted with 126 parents of Slovenian preschool children about early expressive vocabulary. The survey focused on the first five words and the age at which these words were said. Results: The analysis of parental responses showed that the first word in more than half of infants and toddlers occurred before their first birthday. The vast majority, 90 % of toddlers in our sample, had already said at least five words before the age of 18 months. Nouns were the most common word class, followed by verbs and adverbs. Among the first five words, those for naming people from a child’s close environment predominated words for naming other objects and actions. Gender was not statistically significantly associated with the age at first-word acquisition or word-class selection. Conclusion: The research provides an insight into the understanding of fundamental questions on expressive vocabulary acquisition of typically developing Slovenian-speaking infants and toddlers. Furthermore, it provides a good foundation for further research and clinical practice with children involved in speech and language therapy.
Keywords: Child; dojenček; expressive vocabulary; infant; Language; language acquisition; otrok; Slovenian language; slovenski jezik; usvajanje jezika; zgodnji ekspresivni besednjak